A Year in Stanisław Grzepski’s (1524–1570) "De multiplici siclo et talento hebraico" - Linke, Waldemar (Verbum Vitae, 2023)
The article explores Stanisław Grzepski’s workshop of biblical exegesis and his hermeneutics. By analyzing his analysis of the system of biblical measurements and his views on the concept of the year in the Jewish-biblical world – as derived and reconstructed on the basis of textual comparison of the Hebrew, Greek and Latin versions of the Scripture, along with thorough mathematical calculations – one can perceive Grzepski’s approach to the Bible. His hermeneutics, seen against the background of the presuppositions of medieval and Renaissance exegesis, allow the author of the article to draw certain conclusions concerning the threats that also modern exegesis should be cautious of.